COMPARISON OF LIFTNET CATCH USING NEON AND LED LIGHTS IN THE WATERS OF SOUTH BOLAANG MONGONDOW DISTRICT - Olii, Muhammad Yasin Umsini Putra; Marada, Devti Wirnianti; Izza Mahdiana Apriliani; Gillang Fernando (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Fishing with light fishing technology has become a mainstay method for fishermen to attract fish using light. However, the problem of lighting efficiency in this practice is still a concern, especially in the waters of South Bolaang Mongondow Regency, North Sulawesi Province. This study aims to compare the catch results of floating bagan using LED lights and neon lights. The method used is the experimental fishing method, where the fishing process is carried out directly in the field. The catch data was analyzed to calculate the total weight of the catch per trip or hauling in kilograms (kg). The results showed that floating bagan with LED lights produced a catch of 721 kg, while floating bagan with neon lights only produced 495 kg. Statistical analysis showed a significant difference between the two types of lighting. LED lights have the advantage of producing more efficient light intensity and wavelengths that can penetrate deeper waters, making them more effective in attracting fish and increasing the success of the catch. The recommendation from this study is that the use of LED lights can be widely adopted by fishermen as a more efficient and sustainable lighting alternative. Key words: fishing equipment, catchs, lights fishing